2022
DOI: 10.1108/bfj-09-2021-0996
|View full text |Cite
|
Sign up to set email alerts
|

Attracting the millennial customer: the case of food trucks

Abstract: Purpose The purpose of this paper is to examine millennial customer perceptions of food trucks and to identify factors that can foster their behavioral intentions pertaining to food trucks.Design/methodology/approach The study is based on a sample of 247 millennial customers of various food truck vendors in the United States and was assessed using ordinary least squares regression analysis.Findings Food truck image and employee friendliness were found to impact both customer satisfaction and word of mouth beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…The consumer's overall evaluation of the foreign product is measured using five items on a Likert scale anchored by "strongly disagree-strongly agree". This type of scale has been used and continues to be used in a multitude of experimental works (see, for instance, Shafieizadeh et al [33] or Kraus et al [34]). There are different ways of presenting the same scale.…”
Section: Resultsmentioning
confidence: 99%
“…The consumer's overall evaluation of the foreign product is measured using five items on a Likert scale anchored by "strongly disagree-strongly agree". This type of scale has been used and continues to be used in a multitude of experimental works (see, for instance, Shafieizadeh et al [33] or Kraus et al [34]). There are different ways of presenting the same scale.…”
Section: Resultsmentioning
confidence: 99%
“…Brand as a tool for consumers to identify products and as a reference for consumers to evaluate purchases not as an experience, but as a consistent guarantee of brand origin and quality (Nguyen et al 2021). Brands have unique characteristics that differentiate products, and advances in e-commerce have significantly increased the number of brands in the market (Komariah Ulan, Agung Kresnamurti Rivai, and Dewi Agustin Sari 2022) in line with (Kraus et al, 2022). Brand image is often used as an extrinsic guide when consumers evaluate a product before deciding to buy so it can be explained that branding is an important part of a product, be it a product or a service and in the business world, the influence of brand image on purchasing decisions is closely related and cannot be separated (Macheka, Quaye, and Ligaraba 2023).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, this factor is widely discussed, involving cultural (Deng et al, 2022), psychological (Mirosa et al, 2020), biological and many other fields (Andre and Soukoulis, 2020). This study mainly focuses on its basic commodity attributes, which are defined as the quality level of food that can meet consumers' transaction needs in the market environment and measuring it through consumers' subjective evaluation after comprehensive comparison (Yu et al, 2017;Kraus et al, 2022). And consumers' evaluation and perception of food quality is often the basis of establishing psychological contracts with food sales platforms because the basic commodity attribute of this factor determines consumers' psychological cognition of the substantial benefits obtained from the transaction interaction (Shi et al, 2013;Toivonen, 2012).…”
Section: Food Quality and Food Safetymentioning
confidence: 99%
“…It's hard to impress consumers with a single product or service; the same is true of the food trade (Grewal et al ., 2009). Previous studies have found that in addition to food quality, service quality is one of the concerns of food consumers in different traditional transaction places (Jeaheng et al ., 2023); whether it's in a fancy restaurant (Chin and Tsai, 2013), a fast food restaurant (Chun and Nyam-Ochir, 2020), a street stall (Seo and Lee, 2021), a food truck or a supermarket (Kraus et al ., 2022; Bougoure and Lee, 2009).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%